Ticagrelor — a legend of modern cardiology - S. R. Gilyarevsky (Российский кардиологический журнал)
The article presents the evidence on the basis of which the ticagrelor is used in patients with various forms of coronary artery disease, including both acute and chronic. Evidence is provided to support the benefits of ticagrelor over clopidogrel in patients with acute coronary syndrome, as well as the benefits of ticagrelor in combination with a low dose of acetylsalicylic acid (ASA) compared with ASA monotherapy in patients with chronic coronary artery disease. Particular attention in the review is paid to antithrombotic therapy in patients in the long term after myocardial infarction. The rationale for using a low dose of ticagrelor rather than rivaroxaban in this situation is being considered. The advantages of original ticagrelor (Brilinta) rather than generics are being discussed. Data are provided on the pleiotropic effects of ticagrelor, which may have additional positive effects in patients after myocardial infarction, which are manifested in a decrease in the severity of myocardial remodeling. Possible mechanisms causing the pleiotropic effects of ticagrelor, in particular the increase in adenosine levels in tissues, are discussed. Data are presented on the possible effect of ticagrelor on the risk of pneumonia and sepsis, including data obtained in a Mendelian randomization study, which confirms the results of the PLATO study. Overall, the review provides detailed evidence that supports the view that ticagrelor can already be considered a legend of modern cardiology.